KAJIAN PUSTAKA PERBANDINGAN PENINGKATAN LAJU DISOLUSI DENGAN METODE DISPERSI PADAT, MIKRONISASI, DAN KOMPLEKS INKLUSI - Akmaloka Susanto, Gea
Oral administration of drugs is the most popular route because of the ease of application. Oral drugs must be absorbed to obtain good bioavailability in the body. The dissolution process of a drug is the rate determining step for oral absorption. Drug with low dissolution properties will not be absorbed optimally in the gastrointestinal tract and the bioavailability is usually poor. One of the efforts to increase the dissolution rate of the drug can be done by increasing its solubility. Several attempts to increase the solubility and dissolution rate of poorly water-soluble drugs have been developed, including the formation of a solid dispersion system, micronization, and the formation of inclusion complex. The aim of this study is to determine which method is the best among solid dispersion systems, micronization, and inclusion complexes in increasing the solubility and dissolution rate of poorly soluble drugs. The datas was collected from search engines on PubMed, NCBI, Science Direct, Elsevier and Hindawi websites. The inclusive crietias are national or international; original article; written in Bahasa or English; have a DOI (Digital Object Identifier); and using keywords such as ????solid dispersion????, ????micronization????, ????complex inclusion????, and ????dissolution rate?????Based on the literature review, solid dispersion, micronization, and inclusion complex methods can significantly increase drug dissolution rate of poorly soluble drugs. From 8 studies of active substances used, there are 5 drugs that provide the best increase in the dissolution rate using the inclusion complex method, namely naproxsen, indomethacin, glimepiride, norfloxacin, and celecoxib. Meanwhile, the 3 active substances using the solid dispersion method gave the best increase in the dissolution rate including quercetin, telmisartan, and ibuprofen.